Magical Realism as Historical Discourse Reflected on Eka Kurniawan's 'Beauty is A Wound' (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
This study aims to uncover magical realism as historical discourse portrayed in the novel Beauty is A Wound by Eka Kurniawan. Descriptive qualitative method used in this study. The data were collected by reading, classifying and interpreting. The result is the novel Beauty is A Wound has five elements of magical realism as Faris stated, they are; irreducible elements, phenomenal world, the unsettling doubt, merging realms and disruptions of time, space and identity. In relation with magical realism, New Historicism also applied to unearth Indonesia historical discourse since the time of late Dutch colonization, the invasion of Japan, the Independence Era and the New Order Era. Then, the massacre of everyone who were labeled as communist. And the genocide of all the thugs or preman in order to make safer and better society. In this novel, the history of Indonesia was camouflaged and mixed with magical realism because every event that categorized as magical realism led to the past events which related to the history of Indonesia. Keywords: historical discourse, magical realism, new historicism